Self‐service traps inspected by avian and terrestrial predators as a management option for rodents. Issue 1 (9th August 2019) - Schlötelburg, Annika; Plekat, Alexandra; Bellingrath‐Kimura, Sonoko; Jacob, Jens
Abstract: BACKGROUND: Worldwide, serval rodent species are major pests in agricultural landscapes. A vole‐specific tub‐trap combining trapping and natural predators was developed to minimize the migration of rodents into agricultural crops. The trap was tested in enclosures in terms of its trapability of common voles ( Microtus arvalis Pallas) and in the field regarding predator access and removal of voles, both in comparison to a commercially available self‐service trap (standby‐box). RESULTS: The trapability of voles was equal for tub‐traps and standby‐boxes. The removal of voles occurred four times more often from tub‐traps by a wider variety of predators (e.g. smaller terrestrial predators, birds of prey). Visits by predators were most likely if study sites were not surrounded by artificial surfaces (70% visit probability by terrestrial predators) or if they were in areas that were more than 25% (semi)natural (95% visit probability by avian predators). Furthermore, visits by avian predators increased with time and a learning effect could be demonstrated for magpies ( Pica pica L.). From the first to the fifth day, the visit probability of magpies quadrupled. CONCLUSIONS: Visits by predators decreased with increasing cover of artificial surfaces or decreasing cover of (semi)natural areas, proving the importance of (semi)natural areas in the agricultural landscape. Long‐term trials with different baiting techniques and in landscapes characterized by organic farming should be conducted to ensure the regular removal of voles. The use of tub‐traps that are frequently visited by predators could support crop protection, which might limit the use of rodenticide and the associated exposure risk of non‐target wildlife. © 2019 The Authors. Pest Management Science published by John Wiley & Sons Ltd on behalf of Society of Chemical Industry. Abstract : Combining a mechanical barrier (plough furrow), biological control and traps at agricultural field margins could reduce the migration of rodents and use of pesticides. A new tub‐trap was compared to the standby‐box in terms of the trapability of common voles and the removal of voles by predators.